ANALISIS KUALITAS LAHAN DI KABUPATEN PESISIR BARAT PROVINSI LAMPUNG - Utami, Dyah Nursita (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Since 2012, Pesisir Barat district began to separate from Lampung Barat regency under UU No. 22 Tahun 2012. The new autonomous Region (DOB) which is still in the early stages of planning and utilization after the release of its parent district required a potential utilization of natural resources by considering the power of surrounding areas in order to Development progress. Proper land use planning is one of the ways of utilization of natural resources in the Pesisir Barat district through the study of land quality. The results of this land quality analysis will be known to the parameters of land quality that become excellence and limiting factors for the development of land potential in Pesisir Barat district. The parameters of land quality that will be assessed include texture of soil, soil pH, organic C, Nitrogen, potassium, phosphorus, cation-cation can be exchanged such as Ca, Mg, K, Na, cation exchange Capacity (CEC), and base saturation (KB). By knowing the boundary factor, expected improvement recommendation and land use planning in Pesisir Barat district is more appropriate to the condition and potential natural resources of the region. So as to encourage the optimization of natural resources utilization to accelerate development in the district new autonomous Region. Keywords: Land quality analysis, limiting factors, land use, optimization of natural resources AbstrakSejak tahun 2012, Kabupaten Pesisir Barat mulai memisahkan diri dari Kabupaten Lampung Barat berdasarkan UU Nomor 22 Tahun 2012. Daerah otonomi baru (DOB) yang masih dalam tahapan awal perencanaan dan pendayagunaan setelah lepas dari kabupaten induknya diperlukan suatu usaha pendayagunaan potensi sumberdaya alam dengan mempertimbangkan kekuatan wilayah di sekitarnya dalam rangka mendorong kemajuan pembangunan. Perencanaan tata guna lahan yang tepat menjadi salah satu cara pendayagunaan potensi sumberdaya alam di Kabupaten Pesisir Barat melalui kajian kualitas lahan. Hasil kajian analisis kualitas lahan ini akan diketahui parameter-parameter kualitas lahan yang menjadi keunggulan dan faktor pembatas bagi pengembangan potensi lahan di Kabupaten Pesisir Barat. Parameter kualitas lahan yang akan dinilai antara lain tekstur tanah, pH tanah, C organik, Nitrogen, Kalium, Fosfor, kation-kation dapat ditukar seperti Ca, Mg, K, Na, Kapasitas Tukar Kation (KTK), dan Kejenuhan Basa (KB). Dengan mengetahui faktor pembatas, diharapkan rekomendasi perbaikan dan perencanaan tata guna lahan di Kabupaten Pesisir Barat lebih sesuai dengan kondisi dan potensi sumberdaya alam wilayahnya. Sehingga mampu mendorong optimalisasi pemanfaatan sumberdaya alam untuk mempercepat pembangunan di kabupaten daerah otonomi baru. Kata kunci: Analisis kualitas lahan, faktor pembatas, tata guna lahan, optimalisasi sumberdaya alam